Determinants of Infertility in Couples - Tamrakar, Suman Raj; Bastakoti, Rashmi (Journal of Nepal Health Research Council, 2019)
Background: Infertility is defined as a couple’s inability to conceive after a period of twelve months of regular unprotected intercourse. Infertility globally affects approximately 10-15% of couples. This study was carried out to find out the determinants of infertility among infertile couples.Methods: This is a retrospective review of records of 3231 infertile couples in the Department of Obstetrics and Gynecology, Dhulikhel Hospital from January 1, 2008 to June 30, 2018. A total of 3231 infertile couples were evaluated by reviewing their case history including demographic parameters and investigations performed.Results: Mean age of female cases seeking infertility treatment was 26.85 (±4.78) years and that of male cases was 29.81±3.18 years. About three quarter (74.7%) of the cases was of primary type. Almost half of infertility cases (48.8%) were having only female factor. Of the female contributory factors, half of them (52.12%) had ovulatory cause. Male factors contributed 23.9% of cases and 22.7% cases had abnormality in semen analysis while 1.2% had other sexual dysfunction. Mixed type of infertility was seen in 26.6% and unexplained factors had contribution of 14.4%. Conclusions: Primary infertility cases are three times more common in Dhulikhel hospital.Ovulatory cause was the most common contributory factors among female infertile cases while abnormality in semen parameter was the commonest problem among male infertile cases. Thorough evaluation and repeated visits were required to find out the apparent determinants of infertility problem.Keywords: Female factor; hysterosalpingography; infertility; ovulatory dysfunction; semen analysis.